2004
DOI: 10.1242/dev.00937
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel ZP3-independent sperm-binding ligand that facilitates sperm adhesion to the egg coat

Abstract: During mammalian fertilization, sperm adhere to the extracellular coat of the egg, or zona pellucida, in a species-specific manner. In mouse, evidence suggests that sperm recognize and bind to specific oligosaccharide ligands within the zona pellucida glycoprotein, ZP3, viaβ1,4-galactosyltransferase I (GalT I), a lectin-like receptor on the sperm surface. Although in vitro experiments using isolated gametes lend support to this model, recent in vivo studies of genetically altered mice question whether ZP3 and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Moreover, we have shown that mouse eggs exposed to bOF do not acquire resistance to proteinase and, intriguingly, mouse is an exception for the OGP association with the ZP, despite its evidence in the perivitelline space (21). These two issues suggest that in the mouse OGP is unrelated to ZP resistance to proteinases or to sperm-ZP binding, as has been recently described (15).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, we have shown that mouse eggs exposed to bOF do not acquire resistance to proteinase and, intriguingly, mouse is an exception for the OGP association with the ZP, despite its evidence in the perivitelline space (21). These two issues suggest that in the mouse OGP is unrelated to ZP resistance to proteinases or to sperm-ZP binding, as has been recently described (15).…”
Section: Discussionsupporting
confidence: 52%
“…However, it cannot be ruled out that oviductal modifications of the ZP could also involve the coating of ZP sperm-binding sites, representing a different mechanism to select the fertilizing spermatozoon. In fact, previous observations have revealed differences between ovulated and antral follicular mouse oocytes in ZP sites for sperm (15). Whether an equivalent situation occurs in ungulates is unknown.…”
mentioning
confidence: 93%
“…In mammals, CTLs have been shown to affect a variety of important functions mediated by cell-cell interactions, including inflammation, thrombosis, development, and reproductive physiology [6,27,28]. There are more than 120 C-type lectin domain containing proteins predicted from the genome sequence of the non-parasitic nematode C. elegans, some of which have been characterized for their physiologic roles [4,29].…”
Section: Resultsmentioning
confidence: 99%
“…Although little is known about molecular mechanisms of fertilization in hookworms, the in vitro binding specificity of rAceCTL-1 provided the first evidence of its potential role in reproductive physiology, as GlcNAC is a likely to be a major component of the nematode egg membrane [6,28,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation